Kaizen Keselamatan Kerja untuk Mencapai Zero Accident melalui Digitalisasi Aplikasi K3L Patrol: Studi Longitudinal di PT XYZ - Suhartono, Suhartono; Hidayah, Nurulia (JURNAL BIDANG ILMU KESEHATAN, 2026)
This study aims to analyze occupational accident trends during the 2015–2025 period and evaluate the impact of implementing a digitalized K3L Patrol application based on the Kaizen approach on occupational safety performance at PT XYZ . The research employed a quantitative longitudinal design with a quasi-experimental approach by comparing the period before and after the implementation of digitalization, namely the pre-digitalization period (2015–2022) and the post-digitalization period (2023–2025).The secondary data analyzed included the number of occupational accidents, total working hours, and lost workdays. The safety performance indicators used in this study were Frequency Rate (FR), Severity Rate (SR), and Safety-T Score. Data analysis was conducted using descriptive statistics to examine accident trends and inferential analysis using an independent samples t-test to determine differences in safety indicators between the two research periods.The results show that the average Lost Time Injury Frequency Rate (LTIFR) decreased from 1.29 in the pre-digitalization period to 0.76 in the post-digitalization period (a reduction of 41%), although the difference was not statistically significant (t = 2.21; p = 0.054). In contrast, the average Lost Time Injury Severity Rate (LTISR) significantly decreased from 5.05 to 2.03 (a reduction of 60%) with t-test results (t = 2.78; p = 0.024). The Safety-T Score values during the study period were within the ±2 range, indicating that accident variations remained within normal limits (common cause variation).Furthermore, employee participation in hazard reporting increased by 60.7% after the implementation of the digitalized K3L Patrol system. These findings indicate that the digitalization of the safety reporting system based on the Kaizen approach can enhance employee participation in safety monitoring and contribute to reducing the severity level of occupational accidents.This study concludes that the digitalization of the occupational safety system based on the Kaizen approach is an effective strategy to support the improvement of safety culture toward dependent and interdependent levels and to support efforts to achieve zero accidents in industrial environments.